Broad Spectrum Functional Activity of Structurally Related Monoanionic Au(III) Bis(Dithiolene) Complexes - Le Gal, Yann (2022)
The biological properties of sixteen structurally related monoanionic gold (III) bis(dithiolene/diselenolene) complexes were evaluated. The complexes differ in the nature of the heteroatom connected to the gold atom (AuS for dithiolene, AuSe for diselenolene), the substituent on the nitrogen atom of the thiazoline ring (Me, Et, Pr, iPr and Bu), the nature of the exocyclic atom or group of atoms (O, S, Se, C(CN)2) and the counter-ion (Ph4P+ or Et4N+). The anticancer and antimicrobial activities of all the complexes were investigated, while the anti-HIV activity was evaluated only for selected complexes. Most complexes showed relevant anticancer activities against Cisplatin-sensitive and Cisplatin-resistant ovarian cancer cells A2780 and OVCAR8, respectively. After 48 h of incubation, the IC50 values ranged from 0.1–8 µM (A2780) and 0.8–29 µM (OVCAR8). The complexes with the Ph4P+ ([P]) counter-ion are in general more active than their Et4N+ ([N]) analogues, presenting IC50 values in the same order of magnitude or even lower than Auranofin. Studies in the zebrafish embryo model further showed that, despite their marked anticancer effect, the complexes with [P] counter-ion exhibited low in vivo toxicity. In general, the exocyclic exchange of sulfur by oxygen or ylidenemalononitrile (C(CN)2) enhanced the compounds toxicity. Most complexes containing the [P] counter ion exhibited exceptional antiplasmodial activity against the Plasmodium berghei parasite liver stages, with submicromolar IC50 values ranging from 400–700 nM. In contrast, antibacterial/fungi activities were highest for most complexes with the [N] counter-ion. Auranofin and two selected complexes [P][AuSBu(=S)] and [P][AuSEt(=S)] did not present anti-HIV activity in TZM-bl cells. Mechanistic studies for selected complexes support the idea that thioredoxin reductase, but not DNA, is a possible target for some of these complexes. The complexes [P] [AuSBu(=S)], [P] [AuSEt(=S)], [P] [AuSEt(=Se)] and [P] [AuSeiPr(=S)] displayed a strong quenching of the fluorescence intensity of human serum albumin (HSA), which indicates a strong interaction with this protein. Overall, the results highlight the promising biological activities of these complexes, warranting their further evaluation as future drug candidates with clinical applicability.